Constructing two dimensional amide porous polymer to promote selective oxidation reactions. Issue 14 (28th June 2017) - Khatioda, Rajiv; Talukdar, Dhrubajyoti; Saikia, Basanta; Bania, Kusum K.; Sarma, Bipul
Abstract : Rare example of carboxamide linked 2D COF has been synthesized and applied as robust organic catalyst for selective oxidation reactions with no metal add-ons. The reaction undergoes free radical mechanism aided by the conjugated π-cloud and amide functionality present in the COF. Abstract : The covalent organic polymer synthesis is an elegant way to design materials with various topologies and explore new structures and properties. Herein, we report the synthesis of a novel porous polymer framework with the [3 + 2] structure motif via the condensation of 1, 3, 5-benzenetricarbonyl trichloride and p -phenylenediamine. The resulting highly stable mesoporous 2D framework material exhibits continuous conjugation of π-electronic system. Apart from gas adsorption properties, this material shows remarkable catalytic activity manifested by the conjugated π-cloud and amide functionality in selective oxidation reactions. Utmost selectivity of the reaction that exclusively yields aldehydes from benzyl alcohols via a free radical pathway is proposed and demonstrated. This is one of the rare cases of any organic polymer material acting as an outstanding organic catalyst with no metal add-ons.